Understanding Day Care Enrolment Gaps - Jonas Jessen; Sophia Schmitz; Sevrin Waights (Journal of Public Economics, 2020)
We document gaps in day care enrolment by family background in a country with a universal day care system (Germany). Research demonstrates that children of parents with lower educational attainment and children of migrant parents may benefit the most from day care, making it important to understand why such enrolment gaps exist. We carry out complementary decomposition and quasi-experimental analyses making use of a unique data set that records both parental wishes for day care and actual usage. Our decomposition shows that (a) provision-related factors (local shortages and the level of parental fees) explain at least as much of the gaps as differences in parental wishes for day care, and that (b) far more of the gap by parental education is explained (79%) than of the gap by parental migrant status (22%). Our quasi-experimental designs confirm that reducing both parental fees and shortages significantly decreases the enrolment gap by parental education but not by parental migrant status. We discuss implications for policy.
Additional information: The author Sevrin Waights acknowledges funding from a Marie Skłodowska-Curie Actions fellowship under the Horizon 2020 programme (http://dx.doi.org/10.13039/501100007601) of the European Union (Project acronym: PAGE, Grant number: 752053); info:eu-repo/grantAgreement/EC/H2020/752053
Keywords: I24; J13; 330; child care; early education; family background; decomposition; discrimination; synthetic control